Age Differences in Reappraisal of Negative Autobiographical Memories. Issue 2 (15th March 2021) - Hamilton, Lucas J.; Allard, Eric S.
ABSTRACT: Background: Past studies have been equivocal regarding age differences in reappraisal efficacy. Moreover, the use of laboratory-generated stimuli (e.g., images, film clips) may overestimate age differences. Instead, the use of self-relevant stimuli (e.g., autobiographical memory) may better represent the day-to-day implementation of reappraisal. Method: Younger and older adults generated 50 negative memories and provided negativity, positivity, and vividness ratings. One to two weeks later, participants underwent a reappraisal task during which physiological data were collected. Participants implemented one of the three instructions for 30 seconds: remember naturally, increase negative reactions, or decrease negative reactions via a "positivizing" tactic. Results: Prior to the regulation session, older adults rated all memories more positively than younger adults. No age differences in negativity or vividness ratings emerged. After regulation, older adults rated memories more positively, negatively, and vividly than younger adults. Physiological data suggest that reappraisal demands may have been more cognitively demanding for older adults. However, older adults reported higher negativity and positivity than younger adults. Conclusion: This challenges the existing theory regarding age and emotion regulation. We contend that reappraisal was achieved by younger and older adults; however, achievement may have emerged in slightly different ways.